2015
DOI: 10.1111/sms.12487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term training and detraining on VO2 kinetics: Faster VO2 kinetics response after one training session

Abstract: This study examined the time course of short-term training and detraining-induced changes in oxygen uptake ( V ˙ O 2 ) kinetics. Twelve men (24 ± 3 years) were assigned to either a 50% or a 70% of V ˙ O 2 m a x training intensity (n = 6 per group). V ˙ O 2 was measured breath-by-breath. Changes in deoxygenated-hemoglobin concentration (Δ[HHb]) were measured by near-infrared spectroscopy. Moderate-intensity exercise on-transient V ˙ O 2 and Δ[HHb] were modeled with a mono-exponential and normalized (0-100% of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…However, improvements made during the intervention may be lost when the training regimen is interrupted. For example, after 14 days of detraining following an aerobic intervention in a healthy population, peak VO2 significantly decreased [21,22]. In patients with FM, previous studies have shown that most improvements derived from exercise interventions disappeared after the detraining period [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…However, improvements made during the intervention may be lost when the training regimen is interrupted. For example, after 14 days of detraining following an aerobic intervention in a healthy population, peak VO2 significantly decreased [21,22]. In patients with FM, previous studies have shown that most improvements derived from exercise interventions disappeared after the detraining period [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…It is well known that physical training may alter aerobic metabolism during exercise across systemic improvement in O 2 supply, by changes in cardiovascular and respiratory systems, and/or local improvement in muscle capacity to utilize O 2 during exercise [27]. These types of physiological adaptations differ according to the training modalities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Further support is thus provided for these studies that have proposed increased O 2 distribution to the sites of increased metabolic demand playing an important role in the regulation of O 2 during exercise (Murias et al, 2010 , 2011a , 2014 ; McLay et al, 2016a ). For example, improved matching of O 2 delivery to O 2 utilization, which was associated to a faster O 2 kinetics response, has been demonstrated following brief (≤3 sessions) (Murias et al, 2016 ; McLay et al, 2017 ), short-term (~12 weeks) (Murias et al, 2010 , 2011a ) and long-term (Grey et al, 2015 ) training in both young and older participants. Although not investigated in this study, improved matching of O 2 delivery to O 2 utilization within the active tissues can be explained by different structural enhancements related to exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has typically shown a slower rate of adjustment of oxidative phosphorylation ( O 2 kinetics) in older compared to young individuals (Bell et al, 2001 ; Grassi, 2001 ; Hughson et al, 2001 ; duManoir et al, 2010 ; Murias et al, 2014 ; McLay et al, 2017 ). Despite this observation, a faster O 2 kinetics response can be observed in older individuals subsequent to endurance exercise training interventions (Babcock et al, 1994 ; Bell et al, 2001 ; Murias et al, 2010 , 2016 ; Keir et al, 2016 ; McLay et al, 2017 ). This observation demonstrates that this population is still malleable to produce adaptations within the cardiovascular system and within the skeletal muscle (Belman and Gaesser, 1991 ) that would result in a faster adjustment of O 2 at the onset of exercise.…”
Section: Introductionmentioning
confidence: 99%